Comparison of Peripapillary Retinal Nerve Fiber Layer (RNFL) Thickness between the Normal and Glaucoma Eyes with the Same Vertical Cup Disc Ratio (CDR) using Optical Coherence Tomography (OCT) - Ni Gusti Ari Ayu Raiasih; Elvioza Elvioza; Virna Dwi Oktariana; Joedo Prihartono (Majalah Oftalmologi Indonesia, 2015)
Background: Glaucoma is a disease that belongs to a group of neurodegenerative diseases, such as impaired visual field and optic neuropathy with progressive damage to the optic nerve and retinal nerve fiber layer (RNFL) which is caused by the loss of ganglion cells and axon of the optic. Changes in the optic nerve and RNFL may occur prior to the abnormalities of the visual field nerves. Currently, the visual field examination should be performed to diagnose glaucoma but with patient-subjective result. Before it is detectable, visual field abnormalities are likely going to lose its ganglion cells by 40%. The purpose of this study was to assess and compare the peripapillary retinal nerve fiber layer (RNFL) between the normal and glaucoma eyes with vertical cup disc ratio (CDR) 0.4 to 0.7 in eye clinic Cipto Mangunkusumo Hospital (RSCM) Kirana. Methods: A total of 40 eyes of normal group and 34 eyes of glaucoma following Humphrey field analyzer examination and Optical Coherence Tomography (OCT) were evaluated. Peripapillary RNFL thickness between normal and glaucoma eyes were analyzed and compared each other. Eyes of glaucoma group then were grouped into early-stage glaucoma, according to the criteria in the initial stages of the examination results of Humphrey field analyzer. Result of peripapillary RNFL thickness was analyzed to get a cut off value. Results: Peripapillary RNFL thickness in the normal group with vertical CDR 0.4 to 0.7 was 111.3±9.8 μm to 118.0±3.0 μm, and glaucoma groups with vertical CDR 0.4 to 0.7 was 105.6±12.6 μm to 113.7±6.1 μm. Retinal nerve fiber layer thickness in normal group compared to glaucoma group in the superior quadrant, inferior, nasal, temporal and average on CDR 0.4 to 0.7 was not statistically significant (p>0.05), except on vertical CDR 0.6 average peripapillary RNFL (p<0.05). Cut off value of peripapillary RNFL in superior quadrant was 164 μm, inferior 169.5 μm, nasal 82.5 μm, temporal 73.5 μm and average 111.8 μm. Conclusion: There was no difference in changes of peripapillary RNFL along with the progression of vertical CDR but clinically, peripapillary RFNL thickness in glaucoma group is thinner than that of normal group with the same vertical CDR except in temporal quadrant. Keywords: Retinal nerve fiber layer (RNFL), cup disc ratio (CDR), optical coherence tomography (OCT)